The Road Ahead and Beyond: Future Challenges and Opportunities in the Legal Profession. (2021) - Yang, Suhong; Beham, Markus; Duarte, Mauricio; Duggal, Kabir; Navarro, Chandri
Abstract : This panel touched upon the challenges that the ongoing COVID-19 pandemic brought to the international legal profession and explored opportunities for new professionals. The focus lay on practical suggestions for topics to look out for in the near future.